The Correlation of Oral Health Knowledge and Affective with Caries Rate in Rural Communities - Christiana Cahyani Prihastuti; Fitri Diah Oktadewi; Mahindra Awwaludin Romdlon; Amilia Ramadhani; Haris Budi Widodo; Diah Krisnansari; Fitranto Arjadi (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2023)
The results of Riskesdas (Baseline Health Research) by the Indonesian Ministry of Health in 2018 revealed that the caries rate in rural areas was higher than in urban areas. However, the number of villagers receiving dental and oral health care was lower than in urban communities. Karangtengah Village was located in the Baturraden District, Banyumas Regency, which is socio-demographically rural. This study aims to determine the correlation between knowledge and affective of oral health on the caries rate in Karangtengah Village. The study was observational analytical research. Subjects were selected using a purposive sampling technique. The total subjects were 388 residents. The knowledge and affective data were collected using a questionnaire, and the caries rate was scored using DMF-T. Data were analyzed using the Pearson correlation test (SPSS 22). The results revealed that the oral health knowledge and affective of the majority of Karangtengah Village residents were in the moderate category (48.7% and 66.8%, respectively), while the average DMF-T score was 13.12 (very high). The statistical analysis demonstrated no significant correlation between knowledge and DMF-T score and between the affective aspect of oral health and DMF-T score (p0.5).  The moderate category of oral health knowledge and affective aspect in rural areas may not have been applied as oral health behaviors contribute to high dental caries rates.